Mechanization in Ghana: Searching for sustainable service supply models - Diao, Xinshen; Cossar, Frances; Houssou, Nazaire; Kolavalli, Shashidhara; Jimah, Kipo; Aboagye, Patrick Ohene (International Food Policy Research Institute, 2012)
This paper assesses the sustainability of the current supply network for mechanization, given government policy. Stylized models of mechanization supply are developed based on experience in Bangladesh, China, and India during similar stages of agricultural transformation. Ghana’s supply network is then analyzed in light of key lessons from the Asian experience. The analysis focuses on two policy issues: (1) whether the current model promoted by the government has left enough room for the private sector to develop the supply chain, including machinery imports and trade, and (2) whether this model can better link smallholders’ demand for mechanized services to its supply, such that supply can further induce demand and mechanization can broaden its role in agricultural transformation.